FORMULATION OF MICROWATERSHED BASED INTEGRATED DRYLAND AGRICULTURE PROJECTS - Kundu, P.S. (Journal of Soil and Water Conservation, 2022)
About 70% of the net cropped area in the country is under dryland or rainfed agriculture It is estimated that even with all available water resources the irrigated area in the country cannotbe increased beyond 60% of cultivable area Formulation and implementation of integrated dry land agriculture projects, therefore, assumes great importance to meet evergrowing demands of food, fuel and fibre in the country. The strategy, technology and, constraints, methodology for formulation, issues needing attention for implementation and saient features of some dry land agriculture projects formulated have been discussed in the paper.